Mathematical Creative Thinking Ability Viewed By Self-Esteem In Problem-Based Learning With Open Ended Approach - Alfiani, Intan; Dwijanto, Dwijanto; Nur Cahyono, Adi (Universitas Negeri Semarang, 2019)
The aims of this study were to determine the effectiveness of formulate share listen create (FSLC) model with reciprocal teaching approach assisted by Edmodo towards the achievement of students' mathematical literacy ability and describe the profile of students' mathematical literacy ability based on their engagement groups. This research was a mix-methods sequential explanatory design study. The population was 7th grade students of SMP N 4 Semarang in the academic year 2017/2018. The research subjects were determined based on the group of student engagement consisting of upper, middle and lower groups. Data were obtained from engagement questionnaire, mathematical literacy ability test and interview. The results showed that FSLC model with reciprocal teaching approach assisted by Edmodo was effective towards the achievement of students' mathematical literacy ability. In general, the profile of students' mathematical literacy can be stated as follows. The upper group students mastered communication, mathematisation, representation, reasoning and argument, and devising strategy well. Students with middle engagement group could master communication, mathematisation, representation, devising strategy well. While the lower engagement group, students mastered the representation quite well, but they mastered devising strategy and using symbols / languages / operations component in different way. By paying attention to student engagement, teachers can design the right learning strategy according to students circumstances.